A study of the digestion of protein in humans using ileal and faecal assays : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in biochemistry at Massey University - Rowan, Angela Marie (Massey University, 1989)
A study was conducted with 12 adult human subjects including six ileostomates, to determine the digestibility of protein in a single mixed diet. Significant (P<0.05) differences were found between ileal and faecal amino acid digestibility values for most amino acids (histidine, arginine, aspartate, threonine, serine, glycine, proline, valine, leucine, phenylalanine, methionine, cysteine and tryptophan). The ileal digestibility coefficients ranged from 71.5 to 93.6% for glycine and lysine, respectively, whereas the faecal values ranged from 77.9 to 94.7% for glycine and leucine, respectively. The absolute differences between the methods ranged from 0.2 to 15.0% units for alanine/isoleucine and glycine respectively, and the average of the differences was 3.7% units. The ileostomised growing pig (25kg) was investigated as a model animal to allow more routine determination of the ileal digestibility of protein in human foods, and good agreement was found between the species for apparent ileal amino acid digestibility. There were no significant differences between the two species for the apparent ileal amino acid digestibilities of amino acids, except for lysine, glutamate, proline and alanine. The endogenous flows of amino acids at the terminal ileum were determined in both species, following consumption of a single protein-free meal. The amino acid compositions of the protein flows were similar for pigs and humans, with significant differences only being found for histidine, threonine, alanine, valine and methionine. The endogenous flows were used to correct apparent coefficients to give true estimates of digestibility. The latter values indicated near complete absorption of the dietary amino acids for the human subjects and growing pigs. When the interspecies comparison was based on the true digestibility values, there were only significant differences for the amino acids glutamate, phenylalanine, cysteine and methionine. The absolute differences between the mean amino acid digestibility values for each species were smaller for true coefficients than for the apparent values. The daily excretions of deoxyribonucleic acid (DNA) and diaminopimelic acid (DAP) were determined to indicate the levels of bacteria present at the terminal ileum and in the faeces of pigs and humans. There were higher levels of both of these marker compounds in human faeces samples than in ileal digesta. The opposite was observed for DNA in the pig, while the levels of DAP were similar at the two sites. The digestibility of fibre was also determined to indicate the extent of bacterial activity at these sites, and the values were greater in the faeces than in the ileostomy output of both species.
Keywords: Proteins; Absorption and adsorption; Ileal digestibility; Amino acids